Criminological Review of Mugging Crime Cases - Apud Abdul Aziz; Junifer Dame Panjaitan (MultiTech Publisher, 2023)
Crime is a complex phenomenon that can be understood from various different angles. That's why in everyday life we can catch comments about crime incidents that are different from each other. In our experience it turns out that it is not easy to understand crime itself. Efforts to understand this crime have actually been thought up centuries ago by famous scientists. Plato, for example, stated that gold was the source of human evil. Aristotle said that poverty gives rise to crime and rebellion. Great crimes are not committed to obtain what is necessary for life, but for luxury. Criminology is a branch of science that emerged in the 19th century, which is essentially a science that studies the causes and causes of crime. In another sense, seen from a criminological perspective, crime is any specific act or deed whose action is approved by society to be interpreted as a crime. This means that every crime does not have to be formulated first in a criminal law regulation. So every act that is anti-social, detrimental and annoying to society, can be said to be a crime in criminological terms. In this modern era, human growth and development seems to know no boundaries of space and time because it is supported by the rapid flow of information and knowledge of technology. New discoveries in the field of science and technology have a direct influence on human outlook on life which can ultimately change the human outlook on life.